2019
DOI: 10.1016/j.jobe.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and retrofitting of an existing steel structure subjected to wind-induced failure analysis

Abstract: This is a repository copy of Assessment and Retrofitting of an Existing Steel Structure subjected to Wind-Induced Failure Analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Moreover, the cost analysis demonstrated that the strengthening of a greenhouse structure is a very advantageous solution, as the construction cost is low, and it does not interrupt crop production. Another approach could be the evaluation of wind loads with advanced wind models [17] or Computational Fluid Dynamics (CFD) models [18][19][20][21] which may lead to less conservative wind pressures than the requirements of EN13031-1 [1] and, thus, more meticulous design and retrofitting methods.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cost analysis demonstrated that the strengthening of a greenhouse structure is a very advantageous solution, as the construction cost is low, and it does not interrupt crop production. Another approach could be the evaluation of wind loads with advanced wind models [17] or Computational Fluid Dynamics (CFD) models [18][19][20][21] which may lead to less conservative wind pressures than the requirements of EN13031-1 [1] and, thus, more meticulous design and retrofitting methods.…”
Section: Discussionmentioning
confidence: 99%
“…Jacome et al [12] optimized the aerodynamic-induced vibration of the wing based on the uncertainty-based aerodynamic optimization method. Scholars at home and abroad have also carried out related research on steel structures [13], high-rise buildings [14][15][16] and other building structures [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Earthquakes are not the only sources that cause dynamic loads on structures. One of the main dynamic effects that may lead to sudden or progressive collapses is wind [21][22][23][24]. The wind is a very significant factor that leads to lateral loads to which building structures are relatively more sensitive than they are to vertical loads [25].…”
Section: Introductionmentioning
confidence: 99%